**Solve using quadratic formula x ^{2} – 4x + 3 = 0**

## Answer

**x = 3,1**

## Solution

**x² – 4x + 3 = 0**

**Use the quadratic formula to find the solutions.**

-b ± √b² – 4(ac) ÷ 2a

**Substitute the values a = 1, b = -4, and c = 3 into the quadratic formula and solve for x.**

4 ± √(-4)² – 4(1 X 3) ÷ 2 X 1

Simplify the numerator

**Raise -4 to the power of 2.**

x = 4 ± √16 – 4 X 3 ÷ 2

**Multiply -4 by 3**

x = 4 ± √16 – 12 ÷ 2

**Subtract 12 from 16**

x = 4 ± √4 ÷ 2

**Rewrite 4 as 2²**

x = 4 ± √2² ÷ 2

**Pull terms out from under the radical, assuming positive real numbers.**

x = 4 ± 2 ÷ 2

Simplify x = 4 ± 2 ÷2

x = 2 ± 1

x = 2 + 1 or x = 2 – 1

x = 3 or x = 1

The final answer is the combination of both solutions.

**x = 3,1**